Análise dos acidentes de trânsito envolvendo crianças na cidade de Uberlândia: subsídios para as políticas públicas - Freitas, Juliana Pontes Pinto (2013)
All children around the world have the right to a safe environment and protection from accidents and violence (WORLD HEALTH ORGANIZATION WHO, 2008a). The traffic will be the fifth leading cause of death worldwide by the year 2030 and Brazil ranks fifth among the record holders in traffic deaths worldwide. The aim of this work is to analyze traffic accidents involving children from zero to fourteen years old in the city of Uberlândia, in order to support public policies to prevent and reduce these accidents. To achieve the proposed objectives, after authorization given by the command of the 9th Region Integrated of Public Security (9th RISP) and the Minas Gerais 5th Battalion Military of Firefighters, was carried out data collection through police reports of traffic accidents by police and fire departments, cases of children from zero to 14 years old, victims of traffic accidents in the city of Uberlândia in 2010. It was requested from the Department of Nosology of the Uberlândia Federal University Hospital (UFU) the listing of the victims from zero to 14 years old, who were admitted to the hospital due to traffic accidents. We interviewed the parents or caregivers of children victims of traffic accidents after obtained consent, using script interviews with structured and semi-structured questions specially designed for the collection of information. Children victims of non-fatal traffic accidents were also interviewed, after obtained parental consent. Were also interviewed schools representatives in neighborhoods where occurs higher rates of accidents. We identified the conditions of occurrence of accidents, demographic and socioeconomic profile of the victims and the spatial distribution of traffic accidents. The elaboration of territorial diagnostics of living conditions and health situations can lead and facilitate the process of decision-making. It is proposed in this thesis that coping with issues related to traffic accidents are addressed from the perspective of municipal urban planning, traffic and transport, health, education, the driver training system and also the parents and guardians of children.